2005
DOI: 10.1063/1.1993757
|View full text |Cite
|
Sign up to set email alerts
|

Use of patterned laser liftoff process and electroplating nickel layer for the fabrication of vertical-structured GaN-based light-emitting diodes

Abstract: The fabrication process and performance characteristics of a vertical-structured GaN-based light-emitting diode (VM-LED) employing nickel electroplating and patterned laser liftoff techniques are presented. As compared to regular LED, the forward voltage drop of the VM-LED at 20–80 mA is about 10%–21% lower, while the light output power (Lop) is more than twice in magnitude. Especially, the Lop exhibits no saturation or degradation at an injection current up to 520 mA which is about 4.3 times higher than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 17 publications
1
56
0
Order By: Relevance
“…A patterned laser lift-off (LLO) process using a 248 nm excimer laser at a reactive energy of 850 mJ/cm 2 with a single pulse width of 25 ns was subsequently used to remove the sapphire substrate. A laser beam was directed to the back of the transparent sapphire substrate to decompose the GaN present in the substrate into Ga and N 2 [5] followed by heating the sample to about 40°C to remove the sapphire substrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A patterned laser lift-off (LLO) process using a 248 nm excimer laser at a reactive energy of 850 mJ/cm 2 with a single pulse width of 25 ns was subsequently used to remove the sapphire substrate. A laser beam was directed to the back of the transparent sapphire substrate to decompose the GaN present in the substrate into Ga and N 2 [5] followed by heating the sample to about 40°C to remove the sapphire substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Further enhancement of luminous flux, as well as the efficiency and reliability of power LEDs, are very crucial to promoting SSL. For the past decade, efforts to tackle the current crowding issues in high power LEDs by employing various methods such as a vertical-conducting structure [1][2][3][4][5], a current spreading layer (CSL) [6][7][8] and a micro-LED (l-LED) structure [9][10][11][12][13], have been demonstrated. Among these approaches, l-LEDs have been shown having better uniformity in respect to current distribution and enhancement related to light output power (LOP) as compared to that of conventional lateral LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Here, only the thickness of 300 nm was considered because it could make an optimized tradeoff between the sheet resistance and transparency as compared to the other thicknesses. 3,4 It is found that the average transmittances of the 300-nm-thick IZO case are maintained above 84%, which still favors light extraction. To evaluate the contact properties of Ti (1.5 nm)/IZO (300 nm) to the top n-GaN layer, the specific contact resistances using the circular-transmission-line model (CTLM) 17 with six circular test patterns in different dimensions were evaluated.…”
mentioning
confidence: 95%
“…1,2 Recently, many attempts have been made to develop high-efficiency and high-power GaN-based LEDs by transferring the epitaxial structure to a metal or semiconductor substrate using laser lift-off (LLO) techniques for fabrication of vertically structured LEDs (abbreviated as VLEDs). 3,4 However, light extraction efficiency of VLEDs has been deteriorated due to problem of the total internal reflection (TIR), 5 which arises from the large difference in refractive indices between GaN (n ¼ 2.5) and air (n ¼ 1). As a result, the photons generated from active region of LEDs have a very small critical angle (h C ) of 23.5 and the light external efficiency from a flat GaN surface is only $4%, 6 which could be the main challenge in further improving the efficiency and power rating of VLEDs.…”
mentioning
confidence: 99%
“…Surface passivation with appropriate dielectric layers is also necessary to avoid non-radiative recombination for high η rad [2]. Special techniques such as control of surface roughness [3][4][5], preparation of patterned sapphire substrate (PSS) [6,7], application of flip-chip bonding [8][9][10], adaption of laser lift-off process [11], and formation of photonic crystal structure [12] are frequently used to improve η ext , which can be increased by increasing the critical angle for the emitted light through an appropriate modification of the surface of the LED [13,14]. Anti-reflection (AR) coating of dielectric layers is frequently used to reduce the Fresnel reflection at the semicon-ductor-air interface in communication LEDs.…”
Section: Introductionmentioning
confidence: 99%